DISCOVERING WISDOM IN GAYO TRADITION WITH REFERENCE TO ISLAMIC EDUCATIONAL VALUES IN MARRIAGE PRACTICE - Husaini, Husaini (UIN Sumatera Utara, 2020)
Abstract: This study examines the extent to which Islamic Educational Values plays in Gayo marriage tradition. By applying a qualitative research methodology where data is obtained through observation, interview and documentation, this study proposes findings that there are several stages in the process of Gayo tradition cultural marriage, they are muginte, segenap and begenap begur, mujule mas, mah bei and munenes. This study finds out that there are Islamic educational values in each stage of the marriage. In general, the marriage process contains values of faith, worship, morals and social. Until now, Gayo cultural tradition, especially the tradition of marriage, where there are many Islamic educational values in it, it is continued to be passed on by the older generation to the younger generation through exemplary, religious guidance and habituation. The effort to cultivate these values has finally been able to create an Islamic society, the heritage of which continues to the present time in the Gayo community. Keywords: values, Islamic education, marriage, Gayo tradition